Antagonism of Endophytic Bacteria and the Consortium Against Culvularia oryzae Bugnic - Zurai Resti; Martinius Martinius; Yenny Liswarni (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2022)
Endophytic bacteria have several advantages, including controlling plant pathogens and increasing plant growth. As a biological control, endophytic bacteria can suppress the development of plant pathogenic fungi. This study aimed to obtain endophytic bacteria and the consortium of endophytic bacteria that can inhibit the growth of C. oryzae. The study used a Completely Randomized Design (CRD) for studying the ability of endophytic bacteria using eight isolates: Bacillus sp HI, Bacillus sp SJI, B. cereus P14, B. cereus Se07, Serratia marcescens strain JB1E2, S. marces-cens strain JB3, S. marcescens strain ULG1E2 and S. marcescens strain ULG1E4, with three replications. For Studying the ability of endophytic bacteria consortium using six endophytic bacteria consortia and control with three replications. Observations were made on the inhibition growth of C. oryzae. The results showed that all endophytic bacteria and the endophytic bacteria consortium could inhibit C. oryzae, with inhibition of 58.50% – 75.00% and 38.00% – 77.00%. Endophytic bacteria which can significantly suppress the growth of C. oryzae were B. cereus Se07, Bacillus sp HI and Bacillus sp SJI with inhibition of 75.00%, 70.50%, and 70.00%. The endophytic bacteria consortium that had a high ability to suppress the growth of C. oryzae was the consortium of B (S. marcescens strain ULG1E4, S. marcescens strain JB1E3), D (Bacillus sp SJI, Bacillus sp HI, S. marcescenns JB1E3), and G (Bacillus sp SJI, S. marcescens strain ULG1E4), with inhibition of 77.00%, 72.33%, and 71.33%, respectively.